Experiences of Support Staff with Expanding and Strengthening Social Networks of People with Mild Intellectual Disabilities. (23rd July 2013) - van, A. E.; Embregts, P. J. C. M.; Hendriks, A. H. C.; Frielink, N.
ABSTRACT A supportive social network is crucial for facilitating social inclusion. The social networks of people with intellectual disabilities (ID) are often small and typically include very little contact with friends and acquaintances who do not have ID. Professionals can play an important role in strengthening and expanding the social networks of clients. In this study, experiences with interventions aimed at doing this were examined. Six group interviews were held with a total of 27 professionals. The results showed interventions to strengthen social networks (e.g. attention to the maintenance of contact with network members) and interventions to expand social networks (e.g. participation in leisure time activities and working with volunteers). However, a large number of impeding factors was mentioned, such as the limited size of the social networks, characteristics of the client, different perceptions and clients falling between the cracks when it comes to leisure time. The large number of impeding factors shows the strengthening and expansion of social networks to be complicated in actual practice. Recommendations are thus made to strengthen and expand the social networks of clients in an innovative manner which also takes these impeding factors into account. Copyright © 2013 John Wiley & Sons, Ltd.